Neutrinoless Double Beta Decay Experiments With TeO2 Low-Temperature Detectors - Brofferio, Chiara; Cremonesi, Oliviero; Dell'Oro, Stefano (Frontiers in Physics, 2019)
Neutrinoless double beta decay (0νββ) is a powerful tool to investigate Lepton Number Violation (LNV), and the only practical way to assess the nature of the neutrinos. It can therefore provide unique information about the Physics Beyond the Standard Model. If observed, 0νββ would unambiguously demonstrate that neutrinos are Majorana particles and would provide a precise measurement of their mass. Among the many experimental techniques used in the search for this rare process, low-temperature detectors represent one of the most promising choices: they show an excellent energy resolution and can scale to very large masses. In this work, we review the most relevant experiments based on TeO2 bolometers that have been developed and taking data at the Laboratori Nazionali del Gran Sasso (LNGS), Italy, since the early 90's. This 30-years-old effort has led to the design and construction of the CUORE detector, currently taking data at LNGS. The use of low-temperature detectors allows to study the 0νββ of 130Te on both ground and excited states, and to explore different decay mechanisms (“standard” light neutrino exchange, Majoron emission, …). At the same time, the investigation of other rare nuclear physics processes is also possible, such as the two-neutrino double beta decay of 130Te as well as the rare decays (120Te and 123Te). Next generation bolometric experiments anticipate top leading sensitivities. The corresponding challenges in the development of ton-scale, low background detectors are highlighted.